2016
DOI: 10.1021/acs.langmuir.5b04506
|View full text |Cite
|
Sign up to set email alerts
|

Surficial Siloxane-to-Silanol Interconversion during Room-Temperature Hydration/Dehydration of Amorphous Silica Films Observed by ATR-IR and TIR-Raman Spectroscopy

Abstract: Silica has been frequently studied using infrared and Raman spectroscopy due to its importance in many practical contexts where its surface chemistry plays a vital role. The majority of these studies have utilized chemical-vapor-deposited films in vacuo after high-temperature calcination. However, room-temperature hydration and dehydration of thin silica particle films has not been well characterized in spite of the importance of such films as substrates for polymer and surfactant adsorption. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 56 publications
8
95
1
Order By: Relevance
“…A possible explanation for this is that replacing the molecular water on the particle surfaces is straightforward, but reversing the dehydration of silanol groups via hydration of siloxane bridges is more difficult. Recent studies have suggested that, on silica at least, both processes are able to occur [19], but our results suggest that the latter does not occur readily on this particular ionomer glass.…”
Section: Discussioncontrasting
confidence: 88%
“…A possible explanation for this is that replacing the molecular water on the particle surfaces is straightforward, but reversing the dehydration of silanol groups via hydration of siloxane bridges is more difficult. Recent studies have suggested that, on silica at least, both processes are able to occur [19], but our results suggest that the latter does not occur readily on this particular ionomer glass.…”
Section: Discussioncontrasting
confidence: 88%
“…Solutions of 3 a in C 6 D 6 (0.01 m ) were treated with five equivalents of the respective donor molecules, and subsequently IR spectra were measured (Figure ). In C 6 D 6 , 3 a shows two broad absorption bands at 3676 and 3611 cm −1 for intramolecular hydrogen‐bridged silanol moieties . These absorption bands can be attributed to the cis conformer.…”
Section: Resultsmentioning
confidence: 95%
“…The spectrum for 3 a +H 2 O shows two absorption bands at 3590 and 3672 cm −1 for intramolecular hydrogen bridged silanol groups, which is in good accordance with the observations in solution. A broad band between 3300 and 3500 cm −1 is due to bulk water, which seemingly does not interact with 3 a . When D 2 O was used instead of H 2 O, absorption bands for the SiOH moieties (3595 and 3666 cm −1 ) were found, whereas bands at 2500 and 2660 cm −1 can be assigned to bulk D 2 O .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1. Recently, it was pointed out by simulation [15] and experiments [16] that the chemical reaction described by Eq. 1 does occur at room temperature.…”
Section: Discussionmentioning
confidence: 99%